Performance improvement of rosin-based room temperature vulcanized silicone rubber using nanofiller fumed silica. (January 2021) - Yang, Xinxin; Jiang, Zhaoyu; Liu, He; Zhang, Haibo; Xu, Xu; Shang, Shibin; Song, Zhanqian
Highlights: Dehydroabietic acid-modified glycidyloxypropyltriethoxysilane (DAG) was used as cross-linking agent. Nanofiller SiO2 was incorporated into the RTVSR to enhance the properties. The synergistic effect of DAG and SiO2 can effectively improve the mechanical properties. The SiO2 -DAG/RTVSR exhibits better performances than pure RTVSR. Abstract: Room temperature vulcanized (RTV) silicone rubber shows many excellent properties, but its applications are limited due to the poor mechanical properties. To improve the mechanical properties of RTV silicone rubber, dehydroabietic acid-modified glycidyloxypropyltriethoxysilane (DAG) was firstly used as the cross-linking agent to select a best DAG modified RTV silicone rubber with higher tensile strength of 0.65 MPa (DAG/RTVSR). Then different amount SiO2 was added to prepare the SiO2 reinforced DAG/RTVSR and further enhance the properties. The micro- morphology of RTVSR, DAG/RTVSR, and SiO2 -DAG/RTVSR confirmed the uniform dispersion of DAG and SiO2, which results a well chain entanglement and increasing intermolecular interaction. Then, SiO2 -DAG/RTVSR exhibit an obvious improvement of mechanical properties and thermal stability compared with unmodified RTVSR and DAG/RTVSR. This work indicates that the mechanical properties and thermal stability of RTV silicone rubber can be effectively enhanced by the synergistic effect of rosin derivative DAG and SiO2 . Graphical abstract: Image, graphical abstract